Hb Santa Juana (β 108(G10) Asn > Ser): a low oxygen affinity hemoglobin variant in a family of Bosnian background - Wildenberg, Niklas Philipp; Rossi, Corinne; Kulozik, Andreas; Kunz, Joachim (Hematology, 2023)
We present a family that carries the β-hemoglobin variant Hb Santa Juana (HBB:c.326A>G, β 108(G10) Asn>Ser), also known as Hb Serres, in three generations. All affected family members had an anomal hemoglobin fraction as detected by HPLC but normal blood count without evidence of anemia or hemolysis. Oxygen affinity (p50 (O2) = 31.9-40.4 mmHg) was decreased in all probands, compared to 24.9-28.1 mmHg in unaffected individuals. Clinical symptoms likely related to the hemoglobin variant were cyanosis during anaesthesia, while other complaints such as shortness of breath or dizziness were less clearly linked with the hemoglobin variant.